القيم الثقافية والتربوية في أشعار سعد مردف الجزائري ديوان:"مواكب البوح" دراسة وصفية - بكوش, أمامة; فرّوم, هشام (University of Eloued جامعة الوادي, 2024)
تتضافر الجهود لتنشئة الإنسان تنشئة اجتماعية سليمة، ليكون فردا نافعا لمجتمعه، بل ولغيره، وتكوين شخصية منضبطة السلوك، مؤهلة لتحمل المسؤولية، ذات مكانة في المجتمع، مكتسبة للثقافة والمبادئ والقيم، فيكون بذلك فردا صالحا ومصلحا. الشاعر ابن مجتمعه، فله ينتسب، وبقضاياه ينشغل، فمن خلال شعره ينقل ثقافته، ويعبر عن هويته، ويرسخ القيم المختلفة في القارئ، فهو مرآة عاكسة لما في بيئته، كل بحسب انتمائه، وثقافته، فكل قصيدة لها من ثقافة قائلها نصيب. تأتي هذه الدراسة لتسلط الضوء على ديوان "مواكب البوح"، وهو أحد دواوين الشاعر سعد مردف الجزائري المولد والمنشأ، وذلك من أجل الكشف عن القيم الثقافية والتربوية المُضَمَنَة فيه. Abstractː Efforts are combined to raise a person in a sound social upbringing, to be a useful individual to his society, and even to others. And to form a disciplined personality capable to hold responsibility of decent social position in society. Acquired culture, principles and values, and thus be a good and reformed individual. The poet is the son of his society, so he is affiliated with it and preoccupied with it's issues. Through his poetry, he reflects his culture, expresses his identity, and instills different values in the reader. He is a mirror that reflects his environment, each according to his affiliation and culture. Each poem has a share of the culture of its author. This study sheds light on the collection of "Mawakeb Al_Baweh", which is one of the collections of the Algerian-born and originated poet Saad Mirdif, in order to reveal the cultural and educational values contained in it.
مقال. مجلة علوم اللغة العربية وآدابها. مج16 . ع.01. جامعة الوادي
Keywords: الثقافة; التربية; القيم التربوية; القيم الثقافية; مواكب البوح; سعد مردف; culture; education; educational values; cultural values; Mawakeb Al_Baweh; Saad Mirdif.